Rapid diagnosis of Plasmodium falciparum malaria using a point-of-care loop-mediated isothermal amplification device - Puri, Madhu; Kaur Brar, Harsimran; Madan, Evanka; Srinivasan, Rajesh; Rawat, Kapil; Gorthi, Sai Siva; Kumari, Geeta; Sah, Raj; Ojha, Sashi Bhusan; Panigrahi, Subhendu; Dhangadamajhi, Gunanidhi; Muthuswami, Rohini; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
LAMP diagnosis of malaria is simple and cost-effective with acceptable sensitivity and specificity as compared to standard diagnostic modules such as microscopy, RDTs and nested PCR, and thus its deployment for onsite screening of malaria in resource-limited regions is under consideration. However, the requirement of an electricity-operated dry bath and bulky read-out unit is still a major concern. In an effort to simplify this limitation, we have developed a portable LAMP device and fluorescence readout unit which can be used in the rapid point-of-care diagnosis of malaria. We have developed a point-of-care diagnostic LAMP device that is easy to operate by a mobile application, and the results can be quantified with a fluorescent readout unit. The diagnostic performance of the device was evaluated in 90 P. falciparum-infected clinical isolates stored at 4°C for 6-7 years and 10 freshly collected isolates from healthy volunteers. The LOD and quantitative ability of LAMP in estimating parasitemia levels were revealed with laboratory-grown P. falciparum strain (3D7). The LAMP assay performed in our device was exclusive for P. falciparum detection with sensitivity and specificity determined to be 98.89% and 100%, respectively, in clinical isolates. The LOD was documented to be 1 parasite/µl at the cut-off ADC value of 20. Parasite density estimated from ADC values showed concordance with microscopically determined parasite density of the cultured P. falciparum 3D7 strain. The LAMP assay performed in our device provides a possible portable platform for its deployment in the point-of-care diagnosis of malaria. Further validation of the quantitative ability of the assay with freshly collected or properly stored clinical samples of known parasitemia is necessary for field applicability.